Pitch series in chant composition: a demonstration. Issue 1 (2nd April 2018) - BAILEY, TERENCE
ABSTRACT: The exposition of an analytical method that reveals the simple basis of the melodic structure of Western liturgical chants belonging to the two general categories of responsory and antiphon. Included are historical observations meant to explain the origin and evolution of chant-melody in the period from the seventh to the thirteenth century.